Psoriasis part 1 - clinical picture, pathogenesis, systemic treatment - Bogusława Pietrzak; Ewa Zwierzyńska; Emilia Hytroś (Polish Pharmaceutical Society, 2023)
Psoriasis is one of the most common chronic inflammatory dermatoses. Despite many years of research, its etiology is still not fully understood. Various immunological, genetic and environmental factors influence the development and course of the disease. The main symptoms of the psoriasis are usually dry skin lesions covered in scales. They are the result of increased epidermal proliferation and chronic inflammation. However, the clinical picture of psoriasis is diverse and the disease may affect not only the skin but also nails, scalp and joints. The first part of the article presents the clinical picture of the disease, its pathogenesis and the most common comorbidities in patients. In the treatment of psoriasis, phototherapy, local and systemic pharmacotherapy are used, both as a monotherapy or in combination treatment. The choice of therapy depends on the severity and location of psoriatic lesions. The therapy should reduce the symptoms of the disease with a low risk of side effects. The article presents, in accordance with the recommendations of the Polish Society of Dermatology, the possibilities of systemic therapy of psoriasis that are used in patients with moderate and severe form of the disease. The article presents drugs such as methotrexate, acitretin, cyclosporine, fumarate dimethylate, apremilast as well as deucravacitinib which is the newest drug on the global market. This drug has been approved by the EMA in early 2023. The last subsection of the article presents the possibilities of biological treatment of plaque psoriasis and psoriatic arthritis. This therapy is especially recommended in patients who have not achieved improvement using at least two different oral medications and in patients with contraindications to systemic treatment. The subsection about biological treatment includes the description of antibodies available in Polish drug programs. Drugs from the different groups are presented such as TNF-α inhibitors, IL-17 inhibitors, IL-23 inhibitors, Janus kinase inhibitors as well as the drugs from these groups, such as bimekizumab or brodalumab which are not yet available for Polish patients.